2003
DOI: 10.3168/jds.s0022-0302(03)74017-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Concentrations of Linoleic and Linolenic Acids on Extent and Intermediates of Ruminal Biohydrogenation in Vitro

Abstract: Three experiments were conducted by in vitro incubations in ruminal fluid to investigate the effects of pH and amounts of linoleic and linolenic acids on the extent of their biohydrogenation, the proportions of conjugated linoleic acid (CLA) and trans-C18:1 as intermediates, and the ratio trans-10:trans-11 intermediates. The effects of pH and amount of linoleic acid were investigated in kinetic studies, and effects of the amount of linolenic acid were studied with 6-h incubations. With identical initial amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 31 publications
11
73
3
1
Order By: Relevance
“…Moreover, when starch was added to the diet or the substrate, the pH was lowered. Although this precludes any definitive separation between the effects of starch and pH, an effect of pH is consistent with the observations of Troegeler-Meynadier et al (2003), and might be related to a decrease in the activity of D12-isomerases produced by B. fibrisolvens, whose optimal pH is 7.0 to 7.2 (Kepler and Tove, 1967). Consequently, to boost the D12-isomerisation, a preliminary selection of a trans-11 BH microflora by a lowstarch diet is necessary, and addition of LA in the culture, both acting as a BH substrate and increasing E1, optimises the trans-11 isomers balance.…”
Section: Rates and Efficiencies Of Bh Reactionssupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, when starch was added to the diet or the substrate, the pH was lowered. Although this precludes any definitive separation between the effects of starch and pH, an effect of pH is consistent with the observations of Troegeler-Meynadier et al (2003), and might be related to a decrease in the activity of D12-isomerases produced by B. fibrisolvens, whose optimal pH is 7.0 to 7.2 (Kepler and Tove, 1967). Consequently, to boost the D12-isomerisation, a preliminary selection of a trans-11 BH microflora by a lowstarch diet is necessary, and addition of LA in the culture, both acting as a BH substrate and increasing E1, optimises the trans-11 isomers balance.…”
Section: Rates and Efficiencies Of Bh Reactionssupporting
confidence: 62%
“…Troegeler-Meynadier et al (2003) showed that increasing LA concentrations (from 100 to 300 mg of LA in 160 ml flasks, carried by soybean oil), decreased the LA BH efficiency, but increased the amount of LA that disappeared, suggesting a limit of the capacity of isomerisation rather than an inhibition. In our case, 90 mg of LA were added to 120 ml cultures as free FA.…”
Section: Rates and Efficiencies Of Bh Reactionsmentioning
confidence: 99%
“…Total concentrations of CLA were highest in the HF, intermediate in MF, and least in LF indicating that CLA formation is favoured by high ruminal pH. Troegeler-Meynadier et al (2003) also reported more CLA accumulation in rumen cultures incubated at high than low pH. The predominate CLA isomer detected in the HF and LF were c9t11 CLA and t10c12 CLA, respectively.…”
Section: Discussionmentioning
confidence: 78%
“…The biohydrogenation of oleic, linoleic and linolenic acids was greater in HF and MF than LF diet. Wang et al (2002) and Troegeler-Meynadier et al (2003) also reported decreased biohydrogenation of linoleic and linolenic acids at low pH in vitro. Under in vivo conditions, Sackmann et al (2003) and Kucuk and Hess (2004) have shown that higher dietary forage levels increase biohydrogenation of dietary C18 unsaturated FA.…”
Section: Discussionmentioning
confidence: 94%
“…E-mail: john.kennelly@ales.ualberta.ca (Kramer et al, 2004). The concentrations of the intermediates in the rumen depends on the extent to which PUFA substrates are metabolized and are influenced by the initial concentration of dietary PUFA (Harfoot et al, 1973), passage rate, and rumen pH (Troegeler-Meynadier et al, 2003;Qiu et al, 2004). Altered rumen function resulting from a low rumen pH has been demonstrated to reduce the extent of PUFA biohydrogenation both in vitro (Martin and Jenkins, 2002) and in vivo (Kalscheur et al, 1997).…”
Section: Introductionmentioning
confidence: 99%